Chemical Synthesis, Electronic Study, and Vibrational Analysis of a New Organic Copolymer Based on PVK and 3-nhexylthiophene. (20th December 2009) - El Malki, Z.; Hasnaoui, K.; Bouzzine, S. M.; Bejjit, L.; Haddad, M.; Hamidi, M.; Bouachrine, M.
Abstract : Conjugated polymers containing carbazole moieties either in the main or in the side chains have attracted much attention because of their unique electronic properties, to their high photoluminescence quantum efficiency, and thermal stability. The aim of this work is to study a new organic copolymer which combines the PVK properties and those of PHT. We will describe in this study the protocol synthesis, the chemical structure, and the electronic and vibrational properties of the resulting copolymer. The experimental and theoretical studies are combined in order to describe the properties of this material. These properties suggest this compound (PVK-PHT) to be a good candidate for optoelectronic application.